Coating extracellular matrix proteins on a (3-aminopropyl)triethoxysilane-treated glass substrate for improved cell culture - Hiro-taka Masuda; Seiichiro Ishihara; Ichiro Harada; Takeomi Mizutani; Masayori Ishikawa; Kazushige Kawabata; Hisashi Haga (BioTechniques, 2014)
We demonstrate that a (3-aminopropyl)triethoxysilane-treated glass surface is superior to an untreated glass surface for coating with extracellular matrix (ECM) proteins when used as a cell culture substrate to observe cell physiology and behavior. We found that MDCK cells cultured on untreated glass coated with ECM removed the coated ECM protein and secreted different ECM proteins. In contrast, the cells did not remove the coated ECM protein when seeded on (3-aminopropyl)triethoxysilane-treated (i.e., silanized) glass coated with ECM. Furthermore, the morphology and motility of cells grown on silanized glass differed from those grown on non-treated glass, even when both types of glass were initially coated with laminin. We also found that cells on silanized glass coated with laminin had higher motility than those on silanized glass coated with fibronectin. Based on our results, we suggest that silanized glass is a more suitable cell culture substrate than conventional non-treated glass when coated by ECM for observations of ECM effects on cell physiology.